Can we teach students to think like scientists while learning science? - Etkina, Eugenia (Góndola, enseñanza y aprendizaje de las ciencias, 2019)
In the past 20 years the educational community has accumulated enough data to say with conviction that interactive engagement methods lead to better student learning gains than traditional transmission-mode methods (MICHAEL, 2006; FREEMAN et al., 2014). As MITCHELL WALDROP (2015) said “At this point it is unethical to teach in any other way.” But what is this way? There are many models of interactive engagement methods. One popular approach is the “flipped classroom” (FULTON, 2012). In the flipped classroom students read the textbook (or watch a video with the instructor explaining the material), then come to class and discuss what they read through answering questions posed by the instructor. They often work in pairs and participate in voting for the best answer. An example of a flipped classroom in physics education is the method of Peer Instruction (MAZUR, 1997). While the students in these classrooms work collaboratively answering questions and the professor limits lecturing to a minimum, the knowledge that students begin with comes from authority. Students get acquainted with physics concepts by reading the book or watching a video with an authority figure on the screen. While such methods lead to more learning than traditional lecturing, what message about physics are they sending to the students? One answer is that science is an area of study that can be learned by reading the book and discussing what you read in class. Is this the message we want our students to get from our science classes?